Distribusi dan Keanekaragaman Makrozoobentos - Sintia Ananta; Arman Harahap (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the distribution and diversity of macrozoobenthos species in the Barumun River, Kota Pinang District, South Labuhanbatu Regency. The method used is an exploratory method with purposive sampling. The data analyzed were longitudinal distribution, diversity index, evenness index and dominance index. The results showed that there were 15 types of macrozoobenthos with a low diversity index value at all stations. In conclusion, the diversity of macrozoobenthos in the Barumun River is relatively small, so the water quality criteria for this river are categorized as moderately polluted. Keywords: Diversity, Water Quality, Macrozoobenthos, Barumun River